PEMBELAJARAN BAHASA PADA SISWA BERKEBUTUHAN KHUSUS (LANGUAGE LEARNING TO DIS - Warso Nfn (Balai Bahasa Sumatera Utara, 2019)
Language is something that is natural. In essence, all human beings are able to speak in accordance with the conditions of each and languages can also be learned by all human beings. Natural language acquisition will be a positive influence in the continued development of the child's personality. Research and teaching language for public schools and for higher education has been done and contributed greatly to the advancement of education in general. However, the conditions are different, especially for students who have in acquiring language skills. In certain cases, there are students who experienced obstacles in the process of language acquisition and it will make it disturbed in communicating with their environment. Expected more intensive language teachers cooperated with other field experts to address students who experience delays in language acquisition. To foster self-confidence, language skills must be optimized. This situation certainly can not be handled by the teacher. Teachers need to work with various parties such as psychologists, doctors, neurolinguis, and terapilinguis. For a language teacher of the student condition is a noble challenge to maximize the language skills of students with special needs. By understanding the teaching methods for children with special needs and advice from other experts, language teachers will be able to understand the needs of utterances to be trained to the students. The training was based on a function of said tool and the sounds of language that can be produced. Training pronunciation of words that sound close together will facilitate the students with special needs in pronouncing the word and will further foster language skills.